IMPLEMENTASI MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MENULIS CERPEN PADA SISWA KELAS VII E SMP NEGERI 4 KUTA UTARA TAHUN AJARAN 2023/2024 - Laksmi, Ni Nyoman Ayu Tri; Erawan, Dewa Gede Bambang; Putra, I Komang Widana (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research is a classroom action research (PTK) which aims to (1) Knowing that the implementation of SSCS (Search, Solve, Create, and Share) learning can improve activities and learning outcomes of writing short stories in grade VII E students of SMP Negeri 4 Kuta Utara for the 2023/2024 academic year; (2) Know the steps for implementing SSCS (Search, Solve, Create, and Share) learning in improving activities and learning outcomes of writing short stories for grade VII E students of SMP Negeri 4 North Kuta for the 2023/2024 academic year. Data collection is carried out by observation and test methods. The data obtained are then analyzed descriptively, qualitatively and quantitatively. The results of the study showed that the application of SSCS (Search, Solve, Create, and Share) learning methods was effective in improving students' skills and learning outcomes in writing short stories in grade VII E students of SMP 4 North Kuta. The increase in student skills can be seen from the enthusiasm of students in responding to learning. Students are active in learning in class and are able to understand the material and complete the tasks given. Furthermore, when viewed from student learning outcomes, the increase in short story writing results can be seen from the results of assignments given by educators to students and can be reviewed from the average score of student tests. In the precycle stage students obtained an average score of 5.28, in cycle I students obtained an average score of 7.39 and in cycle II students obtained an average score of 8.46. This can be seen from students who are able to string together stories, choose the right words, harmony of sentences with one another and students can create a written work in the form of a short story. Abstrak Penelitian ini merupakan penelitian tindakan kelas (PTK) yang bertujuan (1) Mengetahui implementasi pembelajaran SSCS (Search, Solve, Create, and Share) dapat meningkatkan aktivitas dan hasil belajar menulis cerpen pada siswa kelas VII E SMP Negeri 4 Kuta Utara Tahun Ajaran 2023/2024; (2) Mengetahui langkah-langkah pengimplementasian pembelajaran SSCS (Search, Solvee Create, and Share) dalam meningkatkan aktivitas dan hasil belajar menulis cerpen pada siswa kelas VII E SMP Negeri 4 Kuta Utara Tahun Ajaran 2023/2024. Pengumpulan data dilakukan dengan metode observasi dan tes. Data yang diperoleh kemudian dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukan bahwa penerapan model pembelajaran SSCS (Search, Solve, Create, and Share) efektif dalam meningkatkan aktivitas dan hasil belajar siswa dalam menulis cerpen pada siswa kelas VII E SMP 4 Kuta Utara. Meningkatnya aktivitas siswa tampak dari keantusiasan siswa dalam merespon pembelajaran. Siswa aktif dalam pembelajaran di kelas dan mampu memahami materi serta menyelesaikan tugas yang diberikan. Selanjutnya, jika ditinjau dari hasil belajar siswa, peningkatan hasil menulis cerpen terlihat dari hasil penugasan yang diberikan oleh pendidik kepada siswa dan dapat ditinjau dari nilai rata-rata tes siswa. Pada tahap prasiklus siswa memperoleh nilai rata rata 5,28 pada siklus I siswa memperoleh nilai rata-rata 7,39 dan pada siklus II siswa memperoleh nilai rata-rata 8,46. Hal tersebut dapat dilihat dari siswa yang mampu merangkai cerita, pemilihan kata yang tepat, keselarasan kalimat satu dengan yang lainnya serta siswa dapat menciptakan suatu karya tulis berupa cerpen.